Padrões morfossintáticos variáveis na fala de Quirinópolis-GO: a concordância verbal de terceira pessoa do plural - CV de P6 - Carvalho, Marilda Alves Adão (2018)
This thesis, whose study object focuses on variation of verbal concordance of third person plural forms – CV of P6, under the perspective of the Theory of variation and linguistic change, aims at contributing to describing/explaining social formation of Brazilian Portuguese, taking into account the community of Quirinópolis, in the countryside of Goiás, that, despite being an ‘urban’ community, shows some typical rural features. For this research, speech data were collected through sociolinguistic interviews, performed with 36 informants who were born and raised in this town, did not leave town for more than five (5) years and were sorted according to gender – male and female -, four age groups - 14 to 30 years old; 31 to 45 years old; 46 to 60 years old and over 60 years old and three levels of schooling - 0 to 6 years, 7 to 11 years; and over 11. Of the speech data, we retrieved 1.112 occurences with VC of P6, in which we analyzed the following linguistic variables phonetic salience, subject production and position (variables selected by the Program), subject semantic trait, intervenient material between subject and verb and verb type (variables not selected). For the quantitative data analysis, we used GoldvarbX (2001) software, and the findings indicate a predominance of non-canonical identification of CV of P6 with a frequency of 66.3%, whereas it was 33.7%, favored by informants with older and higher schooling, female and older, by more salient forms, subject before verb and null subject. The social variables, namely schooling and age group, were fundamental to define that in Quirinópolis, regarding the use of CV of P6 there is a change in direction of the plural marker loss in verbs, and there is an increased trend in non-canonical identification of plural in the verbs were seen among younger and less schooled informants. Based on the general result of our study, we verify a linguistic polarization picture in our speech community, due to the distance between the popular variety and the standard one, these varieties being at extreme poles, but on a continuum, from which, according to Bortoni - Ricardo (2005), when considering the rural variety, from which the popular one is product, and the cultured urban variety , the rural-urban variety emerges, and it characterizes Quirinópolis speech, regarding the use of CV of P6.